Spirit și destin sub „teroarea istoriei” - Andrei Milca (Revista de Istorie și Teorie Literară)
The brilliant scholar and the most important encyclopedic Romanian spirit of 20-th century, Mircea Eliade is disputed, even in 2007, the year of his centenary. The controversies are the same in the present with those of the past, which stopped Eliade for obtaining the Nobel Prize: for ,,sympathy“ of the young writer, in ’30’s years, for „the Devil“ — the Iron Guard of Corneliu Zelea Codreanu and Nae Ionescu, the teacher and the mentor of Eliade. A prey of a tumultuous period from the Romanian history Mircea Eliade was unjustly accused for 50 years by Nazism and Fascism, although his „contribution“ in promoting Iron Guard’s ideas was never proved and the arguments of his enemies weren’t so reasonable, in fact. The mystery of this ,,collaborationism* can be explained nowadays — and we’ll understand that the scientist and the pioneer of Myths and Religious Ideas History is one of the most ,,collateral victim of his age. Eliade is out of time with the madness of politics and war, is a man without a fate, a mystical-person of „amplitude“ and full of faith, escaped from his Past and earlier life’s violence by the Exile. He was saved and purified in his mission of a Work and Art under the Sacred signs. An Universal Romanian, the writer realized so well the unhappy context and the way of the Romanian Culture under the tyranny of King Carol the 2-nd, or Gheorghiu Dej and Ceausescu, in communism. He was reborn in the whole world from the Act of Creation: his life out of his birth-country is a ,,trial“, a test of labyrinth and, finally, the teacher was reconsidered like a great intellect, a spiritual historian of the Religions. In the year of his celebration we must approach by Eliade’s creation, without looking back in anger, because, now, he’s worth judged only by his books, not by the youth mistakes, which appear so petty comparative with his international career.